Strategi Promosi dan Kualitas Produk Terhadap Minat Beli Konsumen (Studi Pada UMKM Sekitar Kampus Universitas Nurul Jadid) - Widad, Romzatul; Rahayu, Sri; Wati, Winda; Faizah, Dzurrotul (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The purpose of this study is to identify the influence of promotional strategies and product quality on consumer purchasing interest around the Nurul Jadid University campus. This field research aims to gain a deep understanding of the realities faced by SMEs around Universitas Nurul Jadid through qualitative and inductive approaches. The study uses a descriptive method to examine the current conditions and social dynamics of SMEs in the area, focusing on their challenges and opportunities. Data were collected through direct observation and interviews, providing insights into the social, cultural, and economic factors influencing the success of these businesses. UMKM around Universitas Nurul Jadid use both traditional methods like word-of-mouth and modern strategies via social media to reach a wider audience, particularly female students. Product quality, including raw materials, consistency, packaging, cleanliness, and customer feedback, plays a key role in attracting and retaining customers. The combination of traditional and digital promotion methods, supported by quality products, enhances effectiveness, with innovation and adaptability being crucial for success.